One-Pot Chemoselective Synthesis of 2,4,6,8-Tetrasubstituted Quinazolines via Microwave-Assisted Consecutive Bis-SNAr/Bis-Suzuki–Miyaura Cross-Coupling Reactions - Kabri, Youssef; Crozet, Maxime D.; Redon, Sébastien; Vanelle, Patrice (Synthesis, 2014)
A practical and efficient synthesis of 2,4,6,8-tetrasubstituted quinazolines through one-pot chemoselective sequential bis-SNAr/bis-Suzuki–Miyaura reactions under microwave irradiation is presented. The bis-SNAr reaction occurs selectively at the C-2 and C-4 positions of 6,8-dibromo-2,4-dichloroquinazoline and the bis-Suzuki–Miyaura cross-coupling at C-6 and C-8. This procedure affords convergent synthesis of polysubstituted quinazoline derivatives in high yields in very few steps and tolerates a wide range of boronic acids and amines.
Keywords: quinazoline; Suzuki–Miyaura; chemoselectivity; microwave irradiation; palladium